Dreaming of a remittance house: understanding transnational housing aspirations - Vargas-Silva, C; Boccagni, P (SAGE Publications, 2023)
Migrant housing investments in the countries of origin are a demonstration of their transnational engagement and their potential contribution to local development. Yet, these investments remain relatively understudied on a large scale. In this paper, we explore three related questions on the drivers, prevalence, and development of transnational housing, drawing on an original survey of Ecuadorian and Indian migrants in different European cities. First, what factors account for the likelihood of migrants owning a remittance house? Second, for those migrants without houses abroad, what factors account for the likelihood of aspiring to have a remittance house in the first place, as opposed to “not being interested”? Third, how do factors affecting the likelihood of owning a remittance house compare to those affecting the likelihood of being a remittance house dreamer? Our findings suggest that, among those without a remittance house, the likelihood of being a transnational house dreamer decreases with the length of residence abroad, while the length of stay has no statistically significant impact on the likelihood of transnational house ownership. We also find that migrants with greater economic capacity are less likely to be dreamers and more likely to be transnational house-owners, suggesting that the difference between being a transnational house-dreamer and a transnational house-owner is often financial. Finally, greater attachment to the country of origin increases the likelihood of being both a transnational house owner and a transnational dreamer. We also discuss how the results change across migrant groups and across genders.